Заведомость как обязательный признак преступлений, связанных с публичным распространением ложной информации: актуальные проблемы применения статей 207.1-207.3 УК РФ - Nikhad V. Dunyamalyev (Demidov Law Journal, 2026)
This article is devoted to a comprehensive study of the element of «deliberateness» in crimes related to the public dissemination of false information (Articles 207.1-207.3 of the Russian Criminal Code). An analysis of various doctrinal approaches to the legal nature of deliberateness is conducted, examining it as a special technique of legislative drafting. Particular attention is paid to the analysis of current judicial practice, which reveals significant heterogeneity in the methodological approaches of judicial bodies to establishing the element of deliberateness: from comprehensive examination of the totality of circumstances to simplified objectification of a subjective element. The publication notes that in the context of digitalization of the information space, establishing a person's reliable knowledge of the falsity of disseminated information presents significant difficulty for law enforcement practitioners. The necessity of developing unified methodological guidelines for establishing the element of deliberateness is substantiated, addressed to both judicial bodies and preliminary investigation agencies, which will ensure uniformity of law enforcement practice and prevent violations of the principle of inadmissibility of objective imputation.